The Incidence of Retinal Breaks Induced by Posterior Hyaloid Separation During 27-Gauge Pars Plana Vitrectomy. (March 2019) - Rahman, Rubina; Patil, Ajay; Stephenson, John
Purpose: As advances are made in smaller-gauge vitrectomy, it is important to characterize the associated risks. This allows the surgeon to anticipate complications and appropriately counsel patients. The incidence of iatrogenic retinal breaks in 25- and 23-gauge (G) vitrectomy is known, but no studies exist looking at the incidence in 27G vitrectomy with an attached posterior hyaloid face (PHF). This study set out to characterize the incidence. Methods: A retrospective, consecutive, observational study of patients undergoing 27G transconjunctival sutureless vitrectomy for macular pathology or floaters was conducted. This was a single-surgeon series conducted between 2015 and 2017 at Calderdale Royal Hospital, United Kingdom. Inclusion criteria included only those with an attached PHF at the disc, identified intraoperatively. Results: Data were collected and analyzed in 94 patients. Preoperative diagnosis frequency was as follows: epiretinal membrane 24 (25.5%), macular hole 47 (50.0%), vitreomacular traction 11 (11.7%), and floaters 12 (12.8%). In 82 out of 94 patients (89.1%), 27G vitrectomy was combined with 2.2 mm microincisional phacoemulsification with lens implantation. The incidence of iatrogenic retinal breaks associated with PHF separation during 27G PPV was 17% (16 cases). Conclusions: This is the first study to report the incidence of peripheral retinal breaks induced by PHF separation during 27G vitrectomy. Our single-surgeon case series of 27G PPV for all elective vitreoretinal indications, in eyes with attached vitreous, yielded an iatrogenic break rate of 17%. However, no postoperative retinal detachments followed. Statistical analysis revealed no specific risk factors to be significantly associated with outcome (incidence of retinal tear).